SISTEM PERSAMAAN LINEAR ATAS RING KOMUTATIF - SRRM, Titi udjiani (MATEMATIKA, 2006)
Linear systems equations over commutatif ring are linear systems equations with the coeffici-ents of these equations are elements from commutatif ring. This paper discusses about basic theorems on solution of linear systems equations over commutatif ring. The basic theorems will be found by using characteristic of ideal ,annihilator and rank of coefficient matrices of linear systems equations over commutatif ring. The ideal is generated by minors of coefficient matrices of linear systems equations over commutatif ring. Computing the annihilator of ideal we get the rank of coefficient matrices of linear systems equations over commutatif ring